Prognostic Factors and Treatment Strategies for Elderly Patients with Malignant Meningioma: A SEER Population-Based Study - Feng, Songshan; Li, Jing; Fan, Fan; Wang, Zeyu; Zhang, Qian; Zhang, Hao; Dai, Ziyu; Zhang, Xun; Luo, Peng; Liu, Zaoqu; Zhang, Jian; Liu, Zhuoyi; et al. (Frontiers in Oncology, 2022)
Objective Malignant meningioma (MM) is a relatively rare disease with poor survival. Few studies had focused on MM in the elderly population. This study aims to explore the prognostic factors and optimal therapeutic strategy in elderly patients with MM. Methods We took advantage of the Surveillance, Epidemiology, and End Results (SEER) database to include 275 adult patients with histologically confirmed MM between 2011 and 2018. The Kaplan–Meier curves were plotted by different covariates to reveal the survival probability. Univariate and multivariable Cox proportional hazard regression analyses were applied to identify prognostic factors for cancer-specific survival (CSS). Results The multivariable analysis in the elderly group revealed that when compared with patients receiving gross total resection (GTR), patients receiving biopsy had significantly worse CSS (HR = 3.72; 95% CI: 1.35–10.21; P = 0.011), whereas patients receiving subtotal resection (STR) had nearly the same CSS (HR = 0.83; 95% CI: 0.37–1.86; P = 0.653). Meanwhile, postoperative radiotherapy (PORT) showed no significant association with CSS in the elderly patient group (HR = 0.94; 95% CI: 0.42–2.12; P = 0.888). Conclusion Surgical resection is recommended for elderly patients with MM in the absence of surgical contraindications, but GTR does not present survival benefit in the elderly patients compared with STR. Additional large-scale clinical studies are needed to explore the survival benefit of PORT applied in patients with MM.